PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 026 PADANG MUTUNG KABUPATEN KAMPAR - Abu Hasim; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the fact that science student learning outcomes appear to be low and there are still many students who have not reached the KKM. Of the 20 students only 10 students (50%), which reached the KKM. And 10 students (50%). This research is a classroom action research conducted in Class V SDN 026 Padang Mutung Kabupaten Kampar. Research instruments consisted of a Learning Tool used in this research is guided by the Education Unit Level Curriculum (SBC), known as Curriculum 2006 learning device consists of a syllabus, lesson plans, student worksheets and observation sheet. The first meeting for the first cycle of activity the teachers with an average teacher activity was observed on the second cycle increased compared with the cycle I. At the first meeting I cycle average teacher activity 54% in the category enough, at the second meeting of the average activity teachers increased to 66% also in the category of Good. At the third meeting of the second cycle the average activity of 75% of teachers with good category and the fourth meeting with an average activity of 87% in the category of Very Good. The first meeting of the first cycle an average of 41% of student activity with enough categories, at the second meeting of the average activity increased to 66% in both categories. At the third meeting of the second cycle an average of 83% of student activity in the very good category and the fourth meeting increased compared with the previous meetings by an average of 91% of student activity with very good category. Student learning outcomes after initial data of students worth over KKM only 10 people (50%) after the first cycle an increase of up to 12 people (60%) after the second cycle to be increased up to 16 people (80%) Similarly, the average value average student classically obtained at baseline and after just 61.5 I cycle to increase by an average of 68 and in the second cycle to be increased to 73. This means that the classical value obtained student has above KKM has been determined. Keywords: Learning Model of inquiry, learning outcomes IPA